S110 The relationship between parasternal intercostal muscle electromyogram activity, breathlessness and disease impact in COPD. (December 2018) - Moore, A; Estrada, L; Lozano-García, M; Matcha, N; Cho, PSP; Newlove, K; Paulson, S; Rafferty, GF; Moxham, J; Jané, R; Jolley, CJ
Abstract : Introduction: Breathlessness is a cardinal feature of COPD and is frequently distressing and disabling. Thorough assessment of breathlessness is necessary for its effective management, but this is often not achieved in clinical practice. Although no single tool for subjectively measuring breathlessness and disease impact is universally accepted, the questionnaire based modified (m)MRC Dyspnoea Scale and COPD Assessment Test (CAT) scores are widely used in clinical practice and research. Lung function tests and other objective physiological biomarkers in routine clinical practice correlate poorly with patient-reported breathlessness. Neural respiratory drive (NRD), as quantified by transoesophageal diaphragm electromyography (EMGdi), is closely related to breathlessness during cardiopulmonary exercise testing in COPD. Surface parasternal intercostal muscle EMG activity (sEMGpara) can be used as a non-invasive alternative to EMGdi. This study aimed to investigate the relationship between mMRC dyspnoea, and CAT scores, and sEMGpara in COPD patients at rest and when breathing against an inspiratory threshold load. Methods: sEMGpara was recorded in 17 COPD patients (mean±SD FEV1 51.09%±15.1% predicted, 14 male, age 70.9±6.6 years), breathing against an inspiratory threshold load at 60% of maximum mouth inspiratory pressure (60% PImax). mMRC dyspnoea and CAT scores were recorded pre-protocol at rest. Mean peak root mean square (RMS) sEMGpara per breath was calculated, and relationships with mMRC dyspnoea and CAT scores were determined by correlation analysis. Results: Significant positive correlations were observed between mMRC dyspnoea and sEMGpara at 60%PImax (Spearman r=0.624, p=0.007) and between CAT scores and sEMGpara at 60%PImax (Pearson r=0.497, p=0.042) (figure 1). There were no significant correlations between mMRC dyspnoea score and sEMGpara at rest (Spearman r=−0.048, p=0.853) or FEV1 % predicted (r=−0.143, p=0.584), or between CAT score and sEMGpara at rest (Pearson r=0.107, p=0.682) or FEV1 % predicted (r=−0.081, p=0.756). Conclusion: sEMGpara recorded at 60% PImax, but not at rest, correlated with patient-reported breathlessness and disease impact in COPD. This suggests that sEMGpara recorded at 60% PImax could provide a clinically-useful objective physiological correlate of breathlessness-related quality of life in COPD.